Genetic and cellular basis of cerebral cavernous malformations: implications for clinical management. (8th May 2012) - Bacigaluppi, S; Retta, SF; Pileggi, S; Fontanella, M; Goitre, L; Tassi, L; La Camera, A; Citterio, A; Patrosso, MC; Tredici, G; Penco, S
Abstract : Bacigaluppi S, Retta SF, Pileggi S, Fontanella M, Goitre L, Tassi L, La Camera A, Citterio A, Patrosso MC, Tredici G, Penco S. Genetic and cellular basis of cerebral cavernous malformations: implications for clinical management. Cerebral cavernous malformations (CCMs) are a diffuse cerebrovascular disease affecting approximately 0.5% of the population. A CCM is characterized by abnormally enlarged and leaky capillaries arranged in mulberry‐like structures with no clear flow pattern. The lesion might predispose to seizures, focal neurological deficits or fatal intracerebral hemorrhage. However, a CCM can also remain neurologically silent. It might either occur sporadically or as an inherited disorder with incomplete penetrance and variable expressivity. Due to advances in imaging techniques, the incidence of CCM diagnoses are increasing, and the patient must be managed on a multidisciplinary basis: genetic counselling, treatment if needed, and follow‐up. Advances have been made using radiological and pathological correlates of CCM lesions adding to the accumulated knowledge of this disease, although management of these patients is very variable among centers. This review is aimed at providing an update in genetic and molecular insights of this condition. Included are implications for genetic counselling, and possible approaches to prevention and treatment that derive from the understanding of pathogenetic mechanisms.